Medicine and State Violence - Cuerda, Esther (Conatus - Journal of Philosophy, 2019)
During the last decades, in different places and under different circumstances, some physicians and other health professionals have supported state violence. The Holocaust is a prime example for how doctors can cooperate with the state to plan, give ideological support to and implement violent policies. As a consequence of the Industrial Revolution, people gained access to health promotion and health protection, not as an achievement of the welfare state, but as a tool necessary to maintain healthy and more productive workers. Gradually, all social strata, employees and their relatives gained access to health coverage. Physicians as a group increased in number and changed the structure of their profession by establishing a symbiotic relationship with the state. Between the state and the medical class, different models of cooperation can be distinguished. In general, we can affirm that with the implementation of a public health system, greater interdependence among the state and the medical class was established. In the case of authoritarian or totalitarian regimes, the support of the medical class for violent policies depends on the degree of previous cooperation. National Socialist Germany and the Soviet Union are two striking examples of totalitarian states in which strong public health systems and subsequent close cooperation between the medical class and the state can be observed. In both countries, violent state policies were quickly accepted and integrated into medical practice. Practices such as forced sterilization, murder of patients or experimentation with prisoners were prevalent under National Socialism. The abuse of psychiatry as tool for exerting power was common in the Soviet Union. South American dictatorships constitute examples of totalitarian states with weak previous cooperation between the medical class and the state, as they did not have strong public health systems. In those countries, support for state violence can be found, such as participation of health care professionals in torture or abduction of babies, but cooperation was not as strong as in Nazi Germany or the Soviet Union. In other cases in which no strong previous relationship existed between medicine and the state, authoritarian regimes were not accompanied by medical support for violence, such as in the case of the Rwandan genocide or in Cambodia, where doctors were persecuted and murdered based on their membership of the bourgeois class.